The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.25122/jml-2018-0050
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Burnout – A Cross-Sectional Study Among Mental Healthcare Providers in France

Abstract: Previous studies have established a correlation between empathy and burnout among healthcare providers. The aim of this study is to explore whether empathy – the ability to understand what another person is experiencing, was related to mental healthcare staffs’ burnout. We performed a descriptive, cross-sectional, observational study among medical and nursing mental healthcare staff working in the district of Moselle, France. Participants completed a survey including The French versions of the Jefferson Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 40 publications
7
59
3
Order By: Relevance
“…Observational studies report (among other things) that enhanced empathy reduces mortality by 50% among diabetic patients, 3 reduces symptom burden and improves wellbeing, 6 increases patient enablement, 8 increases patient safety, 5 improves self-efficacy and adherence 9 and reduces practitioner burnout. 4 …”
Section: Benefits Of Empathy (Likely To Favourably Influence Cost-effmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies report (among other things) that enhanced empathy reduces mortality by 50% among diabetic patients, 3 reduces symptom burden and improves wellbeing, 6 increases patient enablement, 8 increases patient safety, 5 improves self-efficacy and adherence 9 and reduces practitioner burnout. 4 …”
Section: Benefits Of Empathy (Likely To Favourably Influence Cost-effmentioning
confidence: 99%
“…The evidence in this area, however, is mixed, with a growing consensus that therapeutic empathy reduces practitioner burnout and increases job satisfaction. 4 Few things are likely to be more costly than losing physicians due to burnout and having to replace them. These long-term human resource outcomes are rarely included in cost-effectiveness analyses but may prove relevant in the evaluation of empathic interventions.…”
Section: Other Considerations For Measuring Cost-effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching strategies can be didactic lectures, small group discussions, workshops, role playing, standardized patients' interviews and real patients' interactions. Studies evaluating long term effects of formal curriculum are generally lacking 15 . The clinical environment, though busy, is an important learning site.…”
Section: Discussionmentioning
confidence: 99%
“…Empathy can impact both job satisfaction and job commitment. For example, empathy makes practicing medicine more meaningful, enhancing the sense of usefulness among medical staff, ensuring better job satisfaction and attenuating burnout [24,[37][38] Similarly, empathy and burnout could be mediated by job commitment [39]. One study found that with more years of experience and greater job commitment, there is a sequential increase in nurses' empathy, so variations in job commitment can improve the relationship between empathy and burnout [39,40].…”
Section: Introductionmentioning
confidence: 99%